Productivity and factor proportions in less developed countries : the case of industrial firms in the Congo - Gouverneur, Jacques (Oxford : Oxford University Press, 1971)
This book is primarily concerned with the problem of long-run changes of techniques, productivity and factor proportions within industrial firms in less developed countries; a smaller part of it is devoted to the question of productivity differentials between firms in less developed and advanced countries.
A revision of the author's thesis, Oxford.
Includes bibliographical references.
osa 28/12/18
Loans
Keywords: Labour productivity; Capital productivity; Industrial management; Factor proportions